High tumour stage and margin clearance are still important prognostic factors for post-mastectomy locoregional recurrence in Malaysia - Choong, L. P.; Taib, N. A.; Rampal, S.; Saad, M.; Bustam, A. Z.; Yip, C. H. (West Asia Organization for Cancer Prevention, 2010)
Background: Locoregional recurrence after mastectomy for breast cancer may predict distant recurrence and mortality. This study examined the pattern and rates of post-mastectomy locoregional recurrence (PMLRR), survival outcome and prognostic factors for isolated PMLRR (ILR) in a breast cancer cohort in University of Malaya Medical Center (UMMC). Methods: We studied 522 patients who underwent mastectomy between 1998 and 2002 and followed them up until 2008. We defined PMLRR as recurrence to the axilla, supraclavicular nodes and or chest wall. ILR was defined as PMLRR occurring as an isolated event. Prognostic factors for locoregional recurrence were determined using the Cox proportional hazards regression model. Results: The overall PMLRR rate was 16.4%. ILR developed in 42 of 522 patients (8.0%). Within this subgroup, 25 (59.5%) remained disease free after treatment while 17 (40.5%) suffered disease progression. Univariate analyses identified race, age, size, stage, margin involvement, lymph node involvement, grade, lymphovascular invasion and ER status as probable prognostic factors for ILR. Cox regression resulted in only stage III disease and margin involvement as independent prognostic factors. The hazard of ILR was 2.5 times higher when the margins were involved compared to when they were clear (aHRR 2.5; 95% CI 1.3 to 5.0). Similarly, compared with stage I those with Stage II (aHRR 2.1; 95%CI 0.6 to 6.8) and stage III (aHRR 4.6; 95%CI 1.4 to 15.9) had worse prognosis for ILR. Conclusion: Margin involvement and stage III disease were identified to be independent prognostic factors for ILR. Close follow-up of high risk patients and prompt treatment of locoregional recurrence were recommended.